Scopolamine Induces Deficits in Spontaneous Object-Location Recognition and Fear-Learning in Marmoset Monkeys - Melamed, Jonathan L.; de Jesus, Fernando M.; Maior, Rafael S.; Barros, Marilia (Frontiers in Pharmacology, 2017)
The nonselective muscarinic receptor antagonist scopolamine (SCP) induces memory deficits in both animals and humans. However, few studies have assessed the effects of amnesic agents on memory functions of marmosets – a small-bodied neotropical primate that is becoming increasingly used as a translational model for several neuropathologies. Here we assessed the effects of an acute SCP administration (0.03 mg/kg, sc) on the behavior of adult marmoset monkeys in two tasks. In the spontaneous object-location (SOL) recognition task, two identical neutral stimuli were explored on the sample trial, after which preferential exploration of the displaced versus the stationary object was analyzed on the test trial. In the fear-motivated behavior (FMB) procedure, the same subjects were submitted to an initial baseline trial, followed by an exposure period to a snake model and lastly a post-exposure trial. All trials and inter-trial intervals lasted 10 min for both tests. Results showed that on the SOL test trial, the saline group explored the displaced object significantly longer than its identical stationary counterpart, whereas SCP-treated marmosets explored both objects equivalently. In the FMB test, the saline group – but not the SCP-treated animals – spent significantly less time where the stimulus had been specifically encountered and more time being vigilant of their surroundings, compared to pre-exposure levels. Drug-related effects on general activity, overall exploration (SOL task) and behavioral response to the aversive stimulus (FMB task) were not observed. SCP thus impaired the marmosets’ short-term ability to detect changes associated with the spatial location of ethologically irrelevant (SOL task) and relevant stimuli (FMB task). Similar results have been reported in other animal species. Marmosets may thus help reduce the translational gap between pre-clinical studies and memory-associated human pathologies.